Problematika Penerapan Kurikulum 2013 pada Mata Pelajaran PAI di SMA Negeri 2 Binjai - Neliwati, Neliwati; Silva, Mona Febrica; Aziz, Muhammad Saif; Sitompul, Cahaya Maharani (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to find out and describe the problems of implementing the 2013 curriculum, and how it is implemented and what are the problems of implementing the 2013 curriculum in the subject of Islamic Religious Education at SMA Negeri 2 Binjai. This type of research includes field research. The approach used in this study is a non-statistical approach, using a qualitative descriptive approach. The data in this study were obtained by interview and observation methods. The results showed that the implementation of the 2013 curriculum in Islamic Religious Education Lessons at SMA Negeri 2 Binjai, the 2013 curriculum has been implemented at SMA Negeri 2 Binjai for more than 4 years, starting from 2017 until now based on government regulations. So far schools and teachers, especially PAI teachers, have made efforts to realize the curriculum itself. However, it is still not fully implementing the 2013 curriculum, because teachers have not been able to develop the curriculum itself with various problems faced by teachers, especially PAI teachers. In practice, there are problems related to the curriculum itself, namely the lack of outreach or guidance regarding the 2013 curriculum, and the lack of preparation in terms of facilities and infrastructure. The problems related to students are the lack of enthusiasm and interest in the learning process of Islamic Religious education and the lack of socialization from the school so that the process of implementing the 2013 curriculum has not been fully implemented and developed.